Panoramic Mapping of Urban Social Sustainability: A 35-Year Bibliometric and Visualization Analysis - Sultana Razia; Siti Hajar Binti Abu Bakar Ah (Journal of Regional and City Planning, 2022)
In recent years, ensuring social sustainability has been a global concern for sustainable urban development in both the academic arena and sustainability science. Many studies have been conducted in this area, but a bibliometric analysis has not yet been done previously. This study identified research streams and research hotspots in the urban social sustainability field based on a bibliometric analysis from 1985 to 2020, involving 1,623 documents from the Web of Science database. We used two software packages, Bibliometrix (Biblioshiny) and VOSviewer, for performance and science mapping analysis. The result showed that this research field is growing fast in multiple disciplines. In the publication trend analysis, we found significant changes since 2015. Analysis of leading countries and institutions revealed that developed countries are performing better than developing countries in producing publications on urban social sustainability. In the content analysis, we selected 214 documents and found that the survey method was the most used. Additionally, we found that 13.08 percent of papers (28 out of 214) used as many as 21 different theories, where ‘stakeholder theory,’ ‘planning theory,’ ‘theory of urbanism as a way of life,’ and ‘theory of good city form’ were significantly used. The findings of this study can assist researchers and practitioners by providing valuable insights into the research area of urban social sustainability.